2018
DOI: 10.1155/2018/7490585
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ki-67 Labelling Index and IL-17A with Pituitary Adenoma

Abstract: The aim of the present study was to determine if the Ki-67 labelling index reflects invasiveness of pituitary adenoma and to evaluate IL-17A concentration in blood serum of pituitary adenoma patients. The study was conducted in the Hospital of Lithuanian University of Health Sciences. All pituitary adenomas were analysed based on magnetic resonance imaging findings. The suprasellar extension and sphenoid sinus invasion by pituitary adenoma were classified according to Hardy classification modified by Wilson. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Obviously, correct assessment of tumor invasion is mandatory for this approach, as is evaluation of proliferation. Indeed, in our review of the literature we found a robust association between proliferation, assayed by Ki-67, and presence of invasiveness with 62% of revised reports suggesting a positive correlation [145][146][147] and 38% indicating an unclear association, albeit with a positive trend [13,148,149]. The controversial data on p53 and Ki-67 expression and correlation with invasiveness might in part be a result of differences in defining invasion, as reported by Sarkar et al [140] and discussed herein.…”
Section: Pathological and Molecular Considerationsmentioning
confidence: 99%
“…Obviously, correct assessment of tumor invasion is mandatory for this approach, as is evaluation of proliferation. Indeed, in our review of the literature we found a robust association between proliferation, assayed by Ki-67, and presence of invasiveness with 62% of revised reports suggesting a positive correlation [145][146][147] and 38% indicating an unclear association, albeit with a positive trend [13,148,149]. The controversial data on p53 and Ki-67 expression and correlation with invasiveness might in part be a result of differences in defining invasion, as reported by Sarkar et al [140] and discussed herein.…”
Section: Pathological and Molecular Considerationsmentioning
confidence: 99%
“…The invasiveness of adenomas and other tumors is also evaluated in terms of pathological parameters, such as mitotic figures, Ki-67 index ( 35 , 36 ) and p53 expression in the malignant tissues ( 26 ). Petry et al.…”
Section: Discussionmentioning
confidence: 99%
“…The patients included 34 males and 39 females, with a median age of 55 years (range 25–73 years) and a median follow-up of 78 months (range 36–121 months). Tumors with Hardy-Wilson classification grade IV and/or Knosp classification grades III and IV ( 32 , 33 ) were defined as invasive. Table I includes the clinical and pathological features of the adenomas.…”
Section: Methodsmentioning
confidence: 99%